2015
DOI: 10.1016/j.ijnonlinmec.2015.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Free energy of the edge of an open lipid bilayer based on the interactions of its constituent molecules

Abstract: Lipid-bilayers are the fundamental constituents of the walls of most living cells and lipid vesicles, giving them shape and compartment. The formation and growing of pores in a lipid bilayer have attracted considerable attention from an energetic point of view in recent years. Such pores permit targeted delivery of drugs and genes to the cell, and regulate the concentration of various molecules within the cell. The formation of such pores is caused by various reasons such as changes in cell environment, mechan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…21 Each amphiphile is considered as a one-dimensional rigid rod with the length ξ. 21,47 Further, according to the observation that the hydrophobic tails of the molecules are oriented along the normal of the cylindrical interface, 16,48 the amphiphiles at any interior point of the centreline scriptC are assumed to be perpendicular to scriptC with a uniform angular distribution (see Figure 1). Hence, it is concluded that the spherical head-groups of amphiphiles lie on a cylindrical surface with a constant circular cross-section.…”
Section: Micro-mechanical Modelmentioning
confidence: 99%
See 4 more Smart Citations
“…21 Each amphiphile is considered as a one-dimensional rigid rod with the length ξ. 21,47 Further, according to the observation that the hydrophobic tails of the molecules are oriented along the normal of the cylindrical interface, 16,48 the amphiphiles at any interior point of the centreline scriptC are assumed to be perpendicular to scriptC with a uniform angular distribution (see Figure 1). Hence, it is concluded that the spherical head-groups of amphiphiles lie on a cylindrical surface with a constant circular cross-section.…”
Section: Micro-mechanical Modelmentioning
confidence: 99%
“…Following Keller and Merchant, 51 we assume that the intermolecular potential Ω( χ , χ ′ , d′ , d ′) between two molecules separated by a distance | χ − χ ′| more than a fixed cutoff distance δ vanishes. In the present setting, δ is required to be small relative to the minimum radius of curvature ℓ introduced in assumption iii, 21,47 so that δ ≪ ℓ . Also, since the potential between a molecule at a given point on the micellar body and other molecules does not exist for the whole length of the micelle, the cutoff distance δ is assumed to be much smaller than the length L of the filament.…”
Section: Micro-mechanical Modelmentioning
confidence: 99%
See 3 more Smart Citations